2008
DOI: 10.1080/14786410701726434
|View full text |Cite
|
Sign up to set email alerts
|

Labdane diterpenes from the rhizomes of Hedychium coronarium

Abstract: A new labdane diterpenoid, (E)-labda-8(17),12-dien-15,16-olide (1) together with eight known compounds, coronarin D (2), coronarin D methyl ether (3), coronarin D ethyl ether (4), isocoronarin D (5), coronarin B (6), labda-8(17),11,13-trien-15,16-olide (7), (E)-labda-8(17),12-diene-15,16-dial (8) and 16-hydroxylabda-8(17),11,13-trien-15,16-olide (9), are isolated from the rhizomes of Hedychium coronarium. Compounds 2-4, 5 and 9 are isolated as mixtures of C-15, C-14 and C-16 epimers, respectively. Their struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…The signals in the low field region of the 1 H and 13 C spectra of 1 which displayed resonances ascribed to a β-olefinic proton at δ H 7.07 (t, J = 7.1 Hz, H-12; δ C 153.4, C-12), an oxymethine proton at δ H 6.06 (d, J = 4.6 Hz, H-15; δ C 100.6, C-15), a quaternary olefinic carbon at δ C 123.2 (C-13), and a lactonic carbonyl at δ C 166.8 (C-16), were all assigned to the α,β-unsaturated γ-lactone ring of partial structure 1a. The above-mentioned spectroscopic data of partial structure 1a were comparable with those of coronarin D [8]. However, there was a significant difference between the α,β-unsaturated γ-lactone rings of both structures.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…The signals in the low field region of the 1 H and 13 C spectra of 1 which displayed resonances ascribed to a β-olefinic proton at δ H 7.07 (t, J = 7.1 Hz, H-12; δ C 153.4, C-12), an oxymethine proton at δ H 6.06 (d, J = 4.6 Hz, H-15; δ C 100.6, C-15), a quaternary olefinic carbon at δ C 123.2 (C-13), and a lactonic carbonyl at δ C 166.8 (C-16), were all assigned to the α,β-unsaturated γ-lactone ring of partial structure 1a. The above-mentioned spectroscopic data of partial structure 1a were comparable with those of coronarin D [8]. However, there was a significant difference between the α,β-unsaturated γ-lactone rings of both structures.…”
supporting
confidence: 61%
“…Unlike the α,β-unsaturated γ-lactone ring in coronarin D which bore a pair of methylene protons at the C-14 position of its skeleton, the corresponding position of partial structure 1a bore an oxymethine proton instead [δ H 5.31 (brd, J = 4.6 Hz, H-14; δ C 75.2, C-14)]. The large downfield shift (+ 42 ppm) of the C-14 resonance of partial structure 1a upon comparison with the corresponding atom in coronarin D strongly suggested that a hydroxyl group was attached to C-14 [8]. The homonuclear coupling between H-14 and H-15 along with the long range heteronuclear correlations between H-12 with C-14 and C-16 provided full support for this structural feature (Fig.…”
mentioning
confidence: 99%
“…3,4 Diterpenes of H. coronarium showed anti-inflammatory and cytotoxic activities. [4][5][6][7][8] However, less attention has been given to its leaves. In the present study, essential oil, methanolic and aqueous extracts of the leaves and rhizomes of H. coronarium were assayed for their antimicrobial, mosquito larvicidal and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Diterpenes of H. coronarium showed anti-inflammatory and cytotoxic activities [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%